Analysis of Efficiency and Productivity with Data Envelopment Analysis and Malmquist Productivity Index at As Syafiiyah Islamic University - Pratignyo, Lisana Sumarah; Supian, Sudradjat; Lesmana, Eman (iora, 2023)
Efficiency is important in the assessment of a performance on an institution or organization. After assessment of efficiency is continued with measurement of assessment in its productivity. The purpose of this paper is to analyse the efficiency and productivity of 7 study programs at As Syafiâ€™iyah Islamic University. The results obtained for the value of efficiency on 7 study programs of 2017/2018-2018/2019 academic year using the Data Envelopment Analysis method is there are 6 study programs as Decision Making Unit (DMU) for 2 years consecutive have a technical efficiency value reach 100% on each DMU. As for the productivity measurement of 7 study programs using the Malmquist Productivity Index method which achieved the highest productivity isÂ Islamic Religious Education Program (PAI) with a Total Factor Productivity (TFP) value of 1.124.